2016
DOI: 10.1111/jfpp.13081
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Stability Study of Peptides from Enzymatically Hydrolyzed Male Silkmoth

Abstract: The antioxidant activity and stability of peptides from male silkmoth hydrolysates (MSH) was studied as antioxidant ingredients in potential food applications. MSH were isolated into five fractions: MSH‐I (MW > 30 kDa), MSH‐II (10–30 kDa), MSH‐III (5–10 kDa), MSH‐IV (3–5 kDa), and MSH‐V (<3 kDa) by ultrafiltration. The antioxidant activity, molecular weight distribution and amino acid contents of each fraction were evaluated. The effects of NaCl, temperature, pH, light intensity and simulated gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 32 publications
(32 reference statements)
5
36
0
6
Order By: Relevance
“…As shown in Figure 2(d), there was no significant change in the activity of ACE-inhibitory peptide under different contents of NaCl (P > 0.05). It was reported that 6% NaCl could decrease the bioactivity of peptide through the reduction of solubility (Liu, Wan, Liu, Zou, & Liao, 2017b). The result in our study may be attributed to the good solubility of ACE-inhibitory peptide in NaCl solution.…”
Section: Food Ingredientssupporting
confidence: 65%
“…As shown in Figure 2(d), there was no significant change in the activity of ACE-inhibitory peptide under different contents of NaCl (P > 0.05). It was reported that 6% NaCl could decrease the bioactivity of peptide through the reduction of solubility (Liu, Wan, Liu, Zou, & Liao, 2017b). The result in our study may be attributed to the good solubility of ACE-inhibitory peptide in NaCl solution.…”
Section: Food Ingredientssupporting
confidence: 65%
“…The DPPH radical scavenging and FRAP of the samples significantly decreased ( P < 0.05) with the increase in pH value above 7. Similar results were also reported for antioxidant peptides extracted from Jinhua ham (Zhu et al ., ) and peptides from enzymatically hydrolysed male silk moth (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…() found that the Fe 2+ ‐chelating ability of antioxidant peptides extracted from Jinhua ham showed no significant change under various NaCl contents treatments. However, the antioxidant activity of male silk moth hydrolysates decreased with the increased concentration of NaCl, which may be caused by a salting phenomenon and reduced solubility of peptides resulted from the increased NaCl gradient (Liu et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Given the growing interest in using underutilized foods as inexpensive sources for the production of bioactive peptides, there has been an upsurge in the number of studies examining the antioxidant properties of peptides generated from hitherto conventionally inedible or non‐conventional foods in recent years. These include hydrolyzates and peptides from the red alga Palmaria palmata (Harnedy et al, ), processed fish wash water (Zhou et al, ), chicken blood cells (Zheng, Si, Ahmad, Li, & Zhang, ), squid pen chitosan (Shavandi et al, ), abalone viscera (Je, Park, Hwang, & Ahn, ), pearl oysters (Ma, Wu, & Li, ), rice bran (Phongthai et al, ), mulberry leaf (Sun et al, ), and silkworm (Liu, Wan, Liu, Zou, & Liao, ). Others include microorganisms and single cell organisms (Alzahrani, Perera, & Hemar, ), blood clam (Chi, Hu, Wang, Li, & Ding, ), and echinoderm byproducts (Mamelona, Saint‐Louis, & Pelletier, ).…”
Section: Production Of Antioxidant Enzymatic Protein Hydrolyzatesmentioning
confidence: 99%